PENGARUH GAYA HIDUP DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA AZWA PERFUME PEKANBARU - Nurhalisa "; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The research conducted at AZWA Perfume Pekanbaru where located in Jl. Teuku Umar No. 79, Rintis, Lima Puluh. The problem in this study is number of buyers has decreasing, percentage of target achievement has decreased, and  the failure of the company’s sales target has not been achieved, this study aims to determine the effect of lifestyle and promotion on purchase decisions at  AZWA Perfume Pekanbaru. In this study use quantitive descriptive with SPSS program. The population in this is are consumers at  AZWA Perfume Pekanbaru. The sampling technique chosen is slovin Formula with a sample 100 respondents. Hypothesis testing uses a simple linear analysis method and multiple analysis with result showing that lifestyle and pricinghave a positive and significant effect on purchase decisionat  AZWA Perfume Pekanbaru. With the calculation of the coefficient of determination (R2) lifestyle on purchase decision  the value of R square is 0,724 or 72,4% and pricing on purchase decision the value of R square is 0,515 or 51,5% and coefficient of determination (R2) lifestyle and pricing on purchase decision the value of R square is 0,747 or 74,7%. This show that the lifestyle and pricinggives an effect of  74,7% on purchase decision  at AZWA Perfume Pekanbaru, while remaining 25,3% is effected by other variables that are not examined in this study. Key words:Lifestyle, Pricing, Purchase Decision